2021
DOI: 10.1145/3434184
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Patient and Caregiver Mutual Support Connections in an Online Health Community

Abstract: Online health communities offer the promise of support benefits to users, in particular because these communities enable users to find peers with similar experiences. Building mutually supportive connections between peers is a key motivation for using online health communities. However, a user's role in a community may influence the formation of peer connections. In this work, we study patterns of peer connections between two structural health roles: patient and non-professional caregiver. We examine user beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…While online authenticity will remain elusive, such afordances and features may bring social media users closer to genuine self-presentation along with network and content separation. Each of these design implications have been suggested in previous work (e.g., [47,52,67,80]), yet expounding the online authenticity paradox provides new insight on how they may be implemented. We describe how each of these design implications helps to either resolve or provide alternative solutions to the challenges the online authenticity paradox highlights, and may enable people to uphold their conception of authenticity as an important personal value.…”
Section: Moving Forwardmentioning
confidence: 83%
See 2 more Smart Citations
“…While online authenticity will remain elusive, such afordances and features may bring social media users closer to genuine self-presentation along with network and content separation. Each of these design implications have been suggested in previous work (e.g., [47,52,67,80]), yet expounding the online authenticity paradox provides new insight on how they may be implemented. We describe how each of these design implications helps to either resolve or provide alternative solutions to the challenges the online authenticity paradox highlights, and may enable people to uphold their conception of authenticity as an important personal value.…”
Section: Moving Forwardmentioning
confidence: 83%
“…This separation can be accomplished via multiple accounts on one platform [68], each of which is tailored for a particular imagined audience [55], or by using privacy afordances to segment content to only some parts of a large, diverse network [73], or by participating in communities in separate online spaces [35,51]. Especially in health contexts, people with similar conditions or diagnoses tend to gather in online spaces where they can share with, form connections with, and receive support from similar others [24,25,47,51,52,67,80]. Additionally, LGBTQ+ people often manage context collapse by tailoring their identity presentations to particular audiences, such as those to whom they have and have not disclosed their LGBTQ+ identity, and by maintaining separate online audiences for these diferent identity performances [20,23].…”
Section: Related Work 21 Sharing Dificult/sensitive Content Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Andalibi & Flood interviewed users of Buddy Project, which connects anonymous youths struggling with mental health [4]. Unlike physical illnesses such as cancer [32,51,89] or rare diseases [52], where research has established that matching based on condition is a crucial goal, [4] found that users should be paired based on shared interests or identity, rather than mental health diagnoses, since over-exposure to the same mental illness can lead to unhealthy comparisons or disordered coping mechanisms. O'Leary et al also affirm the necessity of matching peers based on similarities beyond mental health diagnosis, as well as improving the accessibility of interventions, and proactively providing training to users in order to mitigate risks [67].…”
Section: Algorithmic Scaffolding For Supportive Messaging and Moderationmentioning
confidence: 99%
“…Our results suggest that relatability may be one factor affecting reframe quality. Rather than random matching (as in Flip*Doubt and Koko), matching users based on shared contextual aspects of their lives or identities [4,51,67,88], or allowing users to identify people they'd like to interact with again, may improve reframe quality by allowing crowd workers to better understand the specific context of the task [82]. (2) Selecting 𝑁 .…”
Section: 21mentioning
confidence: 99%